Changes of trends in contraception in pandemic – A hospital-based study - Sarkar, Suvobrata; Bhadra, Banasree; Mukherjee, Jayeeta; Roy Chowdhury, Ranita; Ananya, Arnna (Asian Journal of Medical Sciences, 2022)
Background: With the onset of COVID-19 pandemic, the life of humankind had changed a lot. With a change in health-care approach, contraception became a non-essential service and faced a downfall. Aims and Objective: This study objective is to find out the changes in contraceptive usage in a tertiary care center. Materials and Methods: The study is a retrospective observational study, in which contraceptive usage was compared between 2019 and 2020. Data obtained from record section of the institute were used as source. Attendance in Gynecological Outpatient Department, admission in maternity ward, and delivery rates were also compared between 2 years. Results: Total contraceptive usage was decreased by 11.1% in 2020. Long-acting reversible contraceptives or short-acting both types were decreased in 2020, but maximum decrease was barrier method condom by 25.1% and oral contraceptive pills by 24.9%. Hospital maternity ward admission was less by 7% and delivery rates by 2.4%. Only medical termination of pregnancy showed an increased trend in 2020. Conclusion: Pandemic also had caused a toll in family planning, and thus, overall decrease in usage was seen which can be detrimental to population control.